Validation of the Malay version of the anticipatory and consummatory interpersonal pleasure scale (ACIPS): Comparison between schizophrenia patients and healthy subjects / Kohini C Balasingam - Kohini, C Balasingam (2021)
Background The reduced capacity for social and interpersonal interactions, or social anhedonia, is regarded as an important facet of various psychiatric disorders. Its recognition has many important implications in the clinical setting. Though there are several measures to assess anhedonia, there are very few which specifically target the social aspect. A more recent scale is the Anticipatory and Consummatory Interpersonal Pleasure Scale (ACIPS). The goal of the present study was to validate the Malay version of the ACIPS for use in the Malaysian context. Method The study was cross-sectional in design and consisted of 95 schizophrenia patients and 300 healthy subjects. Participants were given Malay versions of the ACIPS, Snaith Hamilton Pleasure Scale (SHAPS-M), and Beck Depression Inventory (BDI-M) to assess their hedonic capacity. Result The Malay version of the ACIPS exhibited good internal consistency (Cronbach’s alpha = 0.875) and good concurrent validity. Exploratory factor analysis (EFA) yielded a single factor solution. Item 1 on the scale did not correlate with the other items. Receiver Operating Characteristics (ROC) analysis demonstrated a cut-off value of 90 on the Malay version of the ACIPS to distinguish between schizophrenia patients and healthy subjects. This score had a sensitivity of 89.4%, specificity of 83.7%, positive predictive value of 63.5%, and negative predictive value of 96.1%. Conclusion The Malay version of the ACIPS is a promising tool with good validity and reliability for assessing overall social anhedonia. Additionally, it is relatively short and easy to administer, making it useful in the clinical setting. Keywords: social anhedonia, schizophrenia, Malaysia, ACIPS, validation